Aesthetics, Psyche and Media: A Manifold of Mimesis in the Age of Simulation - Todorović, Tanja; Janeš, Luka; Novaković, Vanja (Conatus - Journal of Philosophy, 2022)
Within a dialogue with various authors, it seems that there can’t be just one universal reflection that allows us to comprehend the rising dynamism of new media. For example, Baudrillard declared the end of the traditional way of thinking about contemporary media and showed their role in the process of the endless simulation of truth. It has been shown that the contemporary world of media can be considered in dialogue with the philosophical tradition, and be evaluated in the phenomenological psychopathology (Fuchs) evaluation horizon. In this consideration, the notion of variation (Manovich), plays a key role in replacing the traditionally understood notion of mimesis. Artistic practice is precisely the main exemplar that shows the influence of new media on identity construction (simulated versions of personal identity), as well as the relationship between the artistic original and the copy. Although new digital media allows maintenance of desired (identity) simulations, its great potential is evident in enabling subjects to express their individuality, as well as in searching for new ways to improve their quality of life. This context opens a new problem, namely the one of avatar – a selected photo or image that defines the identity of entities present in the fields of the virtual agora (Baudrillard) and private chat rooms of the social media. Avatar`s function is being problematized by asking whether they represent the reduction and closure of the width of a person’s beingness within the set image, or whether they facilitate and stimulate its realization by depriving them of the stress and discomfort that is caused by physical confrontation and intercourse with other persons in the living space. The given issue inevitably points to the problem of the general narcissism of our culture (Lasch), calling upon philosophical orientation to enter the discussion.